Assertive Speech Acts in Gender-Based Product Promotion: A Pragmatic Approach in Business English - Hidayatulloh, Aris; Winarti; Salsabila, Arifah Qurotu Aini Nur; Budiarti , Mukie Ardya (Universitas Islam Negeri Raden Mas Said Surakarta, 2026)
This study employs a pragmatic approach, focusing on assertive speech acts based on Searle's (1985) theory. The data sources are the utterance of the product promotion videos created by undergraduate management students at Universitas Duta Bangsa Surakarta which includes the perspective of product promotion based on the gender. The products are classified using the FCB Grid marketing model to specify the object. The classification of products based on the FCB Grid model considers their involvement level and emotional or rational appeal. This model helps identify the product types promoted by students, providing a foundation for selecting videos for analysis. Speech act analysis focused on identifying dominant patterns and exploring the potential effects of additional subcategories on communication strategies. The findings reveal that among the four types of products promoted, the assertive speech acts included informing, stating, and claiming. Specifically, promotions for high-involvement products, such as roller skates and cosmetics, featured a wider range of assertive speech acts, including four subcategories. The assertive speech acts like insisting and predicting emphasizes the products in Roller blade and Cosmetics video promotion.